Performa Kinerja Keuangan Bank Umum Syariah Periode 2018-2021: Pendekatan RGEC - Adelia Wibisono Wibisono; Dahruji Dahruj (Prodi Ilmu Manajemen, Fakultas Ekonomi Universitas Muhammadiyah Cirebon, 2023)
Based on the formulas laid forth in OJK Circular Letter No.10/SEOJK/03/2014 about Bank Health Level utilizing the RGEC technique, this study was developed to ascertain the soundness level of BUS. The RGEC approach uses a risk factor profile (bank risk), GCG factor (growth, competition, and government), profits, and capital as indicators of performance. All Islamic financial institutions that are OJK-approved throughout the 2018-2021 study period serve as research items. To do this, the RGEC method was used to compute financial ratios, making this research a descriptive quantitative analysis. According to the findings of this analysis, Bank BCA Syariah, Bank Aceh Syariah, Bank BTPN Syariah, and Bank NTB Syariah are among the group of banks that are in very good health between 2018 and 2021. Panin Dubai Syariah Bank may be near the bottom of the ratings, but its performance is not that much below the norm, therefore the bank's overall composite score is still rather good. Keywords: Bank soundness, RGEC, Financial Ratio